2013
DOI: 10.1080/09712119.2012.742442
|View full text |Cite
|
Sign up to set email alerts
|

ThePRNP ins/deland octapeptide repeat polymorphisms in Jersey cattle and their associations with production traits

Abstract: So far the studies on the prion protein (PRNP) gene have mainly been focused on the search for an association between detected polymorphisms in this gene and the susceptibility of cattle to bovine spongiform encephalopathy. The PRNP gene location on chromosome 13 suggests that the polymorphisms within this gene can be potential quantitative trait locus (QTL) markers for milk production traits. The aim of this study was the analysis of the potential effect of the insertion/deletion polymorphisms within the prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In view of the previous reports, the polymorphisms of PRNP were mostly found to linked to BSE (Sander et al 2005), in addition, some of them were also detected to be associated with some phenotypic traits in cattle (Rzewucka et al 2013;Yang et al 2016), sheep (Brandsma et al 2004;Isler et al 2006;Ioannides et al 2009) and goats (Lan, Zhao, Li, et al 2012;Lan, Zhao, Wu, et al 2012). In detail, the prion octapeptide-repeat polymorphisms were reported to significantly affect milk traits in Latxa dairy sheep (Vitezica et al 2013); In Texel sheep, the PrP genotypes were significantly associated with the litter size and weight at 135 days (Brandsma et al 2004); In the ovine PRNP, the VRQ and ARQ allelic variants (locating on codons 136, 154 and 171) were associated with high scrapie susceptibility, which also led to a significant production loss (Ioannides et al 2009); The 28-bp indel within the promoter region in goat PRNP was associated with production traits in Chinese native breeds (Lan, Zhao, Li, et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In view of the previous reports, the polymorphisms of PRNP were mostly found to linked to BSE (Sander et al 2005), in addition, some of them were also detected to be associated with some phenotypic traits in cattle (Rzewucka et al 2013;Yang et al 2016), sheep (Brandsma et al 2004;Isler et al 2006;Ioannides et al 2009) and goats (Lan, Zhao, Li, et al 2012;Lan, Zhao, Wu, et al 2012). In detail, the prion octapeptide-repeat polymorphisms were reported to significantly affect milk traits in Latxa dairy sheep (Vitezica et al 2013); In Texel sheep, the PrP genotypes were significantly associated with the litter size and weight at 135 days (Brandsma et al 2004); In the ovine PRNP, the VRQ and ARQ allelic variants (locating on codons 136, 154 and 171) were associated with high scrapie susceptibility, which also led to a significant production loss (Ioannides et al 2009); The 28-bp indel within the promoter region in goat PRNP was associated with production traits in Chinese native breeds (Lan, Zhao, Li, et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In cattle, several studies recently revealed a large allelic variability at the PRPN and PRND loci [ 49 51 ] and also associations with susceptibility to BSE [ 52 54 ]. A recent investigation on the possible association between polymorphisms of the PRPN gene and milk production traits in cattle led to statistically significant results for milk fat content [ 55 ]. Using the same data as in our study but with a different approach, Mancini et al [ 41 ] detected a signature of selection at the same position on BTA13 and identified the CDP - diacylglycerol synthase ( CDS2 ) gene, which is involved in the phospholipid biosynthetic process.…”
Section: Discussionmentioning
confidence: 99%